Developmental efficacy of the export-oriented clothing industry : the Jamaican case. - NURSE, Keith (1995)
Examines the performance of export-oriented industrialization and export-processing zones in Jamaica in terms of export growth, employment and income generation, foreign exchange earnings, local value-added, technology transfer, the training of personnel, and in general, the promotion of industrial development. Concludes that this mode of peripheral specialization has limited developmental potential for Jamaica, and other Caribbean countries, beyond providing some additional employment opportunities.